2016
DOI: 10.1186/s12913-016-1700-3
|View full text |Cite
|
Sign up to set email alerts
|

Central intake to improve access to physiotherapy for children with complex needs: a mixed methods case report

Abstract: BackgroundChildren with complex needs can face barriers to system access and navigation related to their need for multiple services and healthcare providers. Central intake for pediatric rehabilitation was developed and implemented in 2008 in Winnipeg Manitoba Canada as a means to enhance service coordination and access for children and their families. This study evaluates the process and impact of implementing a central intake system, using pediatric physiotherapy as a case example.MethodsA mixed methods inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…12 The studies were published between 2004 and 2017, with most published after 2010. 6,11,[16][17][18][19] Overall, 9 articles used a simple comparative study design (pre-implementation v. post-implementation), 6,[10][11][12]14,15,[17][18][19] and 1 was cross-sectional. 16 The setting for evaluation of a single-entry model was surgery (orthopedics and general surgery) in 3 studies, 10,12,16 internal medicine (gastroenterology, rheumatology, cardiology, general internal medicine and nephrology) in 5 studies, 6,14,15,17,19 chronic pain in 1 study 11 and physiotherapy in 1 study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The studies were published between 2004 and 2017, with most published after 2010. 6,11,[16][17][18][19] Overall, 9 articles used a simple comparative study design (pre-implementation v. post-implementation), 6,[10][11][12]14,15,[17][18][19] and 1 was cross-sectional. 16 The setting for evaluation of a single-entry model was surgery (orthopedics and general surgery) in 3 studies, 10,12,16 internal medicine (gastroenterology, rheumatology, cardiology, general internal medicine and nephrology) in 5 studies, 6,14,15,17,19 chronic pain in 1 study 11 and physiotherapy in 1 study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…16 The setting for evaluation of a single-entry model was surgery (orthopedics and general surgery) in 3 studies, 10,12,16 internal medicine (gastroenterology, rheumatology, cardiology, general internal medicine and nephrology) in 5 studies, 6,14,15,17,19 chronic pain in 1 study 11 and physiotherapy in 1 study. 18 All but one of the studies were conducted in a single-payer health care system, 6,[10][11][12][14][15][16][17][18] the exception involving a 2-tier system. 19 Three studies required mandatory implementation of a single-entry model, 14,18,19 whereas 7 reported on optional implementation.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 20% to 30% of patients with ankle sprains will develop chronic ankle instability, which will cause repeated ankle sprains, joint relaxation or stiffness, traumatic arthritis, and cause joint dysfunction, which will seriously affect patients' daily lives. Surgical treatment should be given high attention [12]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Biofeedback technology has been used as an adjuvant treatment method for the treatment of post-stroke hemiplegia and the rehabilitation of neuromuscular function for more than 40 years. With the advancement of science and technology, biofeedback technology treatment measures have been greatly improved and gradually become stroke rehabilitation [10]- [14]. One of the comprehensive measures is for effective treatment [15]- [18].…”
Section: Introductionmentioning
confidence: 99%